Computer-aided control system design - Yu, Li. (2008)
This project provides a software package to help the control designer determine the time delay margin for closed-loop stability of a SISO plant with time delay uncertainty. This can save the designer time and effort as is required under conventional methods. In other words, the software provides a solution to the question: what is the largest value of the limiting time delay, below which a controller can exist such that the closed-loop system remains stable.